2022
DOI: 10.29052/ijehsr.v10.i3.2022.296-303
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of self-care in heart failure patients at a cardiac hospice in Peshawar, Pakistan.

Abstract: Background: The significance of self-care in heart failure is yet to be demonstrated empirically; however, it's commonly believed that effective self-care delays the development of heart failure. This study aimed to assess the level of self-care among patients with heart failure attending a cardiac hospice center in Peshawar, Pakistan. Methodology: A cross-sectional study design was used to examine self-care maintenance, self-care management, and self-care confidence in heart failure patients at Heart Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Similarly, another study reported that 54.9% of congestive heart failure (CHF) patients were categorized as class II, and 31.3% fell into class III. 19 These findings align with another study indicating better outcomes for NYHA class I and class II compared to class III and class IV, potentially due to inadequate self-care and physical activity among patients. Therefore, it is recommended to provide enhanced attention and improved care for patients classified as NYHA class III and class IV.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, another study reported that 54.9% of congestive heart failure (CHF) patients were categorized as class II, and 31.3% fell into class III. 19 These findings align with another study indicating better outcomes for NYHA class I and class II compared to class III and class IV, potentially due to inadequate self-care and physical activity among patients. Therefore, it is recommended to provide enhanced attention and improved care for patients classified as NYHA class III and class IV.…”
Section: Discussionsupporting
confidence: 88%
“…Another study conducted in Peshawar, Pakistan, reported diabetes and hypertension as the dominant comorbid conditions, with hypertension alone following closely. 19 In the current study, NYHA class II was the most common classification (34.4%) seen, followed by class III (30.3%).…”
Section: Discussionmentioning
confidence: 48%